Affective Aspect And Speaking Skill Of The Students Of English Education Program - Farid Noor Romadlon; Roro Dwi Astuti (Eduvest - Journal of Universal Studies, 2022)
This study was designed to investigate the relationship between affective aspects (emotional intelligence) and the speaking skill of students in the English Education study program, as well as the relationship between fifteen elements in the affective aspect (emotional intelligence) and the speaking skill of students in the English Education study program. Sources of data from this study were 120 students from the English Language Education study program at Muria Kudus University. They filled out a Bar-on (1997) Emotional Intelligence questionnaire which was used as an instrument and an online interview whose results were analyzed using Cambridge English Assessing Speaking Performance – Level C1. The results of the analysis using the correlation method show that there is a positive relationship between the affective aspects of students' emotional intelligence from the English Education study program and their speaking skill. Furthermore, this study found that there was a significant positive relationship of the fifteen elements in the affective aspect of emotional intelligence with students' speaking ability. In addition, the results of this analysis indicate that the affective aspect can significantly predict students' speaking ability using the Cambridge speaking ability assessment sheet.